1
$\begingroup$

I am working through Stirzaker and Grimmett and found a problem and its solution that I was having difficulty understanding. It has been a while since I really played around with power series, so I might be missing some trick here.

The question is:

Find the generating function of the following mass function

$$ f(m) = \binom{n+m-1}{m}p^n(1-p)^m, \ \ \text{for} \ m \geq 0 $$

The solution, which is provided, is that the generating function $G(s)$ is:

$$ \Big\{\frac{p}{1 - s(1-p)}\Big\}^n $$

I was not sure how the authors arrived at this solution. It looks like they use the normal trick for a geometric series where:

$$ \sum^\infty_{k=1}ar^k = \frac{a}{1-r} $$

but I was not sure how they got the generating function above to fit into this form. Any help is appreciated.

$\endgroup$
  • $\begingroup$ Hint: Differentiate $$\sum^\infty_{k=0}ar^k = \frac{a}{1-r}$$ on both sides with respect to $r$, $n-1$ times and see what you get. Notice the lower limit on that sum is $k=0$ btw. $\endgroup$ – N. Shales Aug 25 '17 at 22:59
  • 1
    $\begingroup$ Thanks @N.Shales I will give that a shot. I appreciate it. $\endgroup$ – krishnab Aug 25 '17 at 23:03
  • 1
    $\begingroup$ If you manage to solve your problem then I suggest you post it as an answer here as I believe that is looked upon favorably by the MSE community. $\endgroup$ – N. Shales Aug 25 '17 at 23:08
  • $\begingroup$ The final formula in this table may help: en.wikipedia.org/wiki/… $\endgroup$ – user940 Aug 25 '17 at 23:23
  • $\begingroup$ Have you learn about the negative binomial distribution and probability generating function? en.wikipedia.org/wiki/Negative_binomial_distribution Essentially for a given pmf, it can be generated by the corresponding pgf. The pgf is given by $\displaystyle G(s) = E[s^X] = \sum s^x f_X(x)$ $\endgroup$ – BGM Aug 26 '17 at 7:19
2
$\begingroup$

For $n\geq 1$, note that $$ \frac{1}{(1-x)^n}=(1-x)^{-n} =\sum_{m=0}^{\infty}\binom{-n}{m}(-1)^{m}x^{m} =\sum_{m=0}^{\infty}\binom{n+m-1}{m}x^{m}\quad (|x|<1)\tag{1} $$ by the extended binomial theorem. In particular, it follows that $$ \frac{p^n}{[1-s(1-p)]^n}==\sum_{m=0}^{\infty}\binom{n+m-1}{m}p^n(1-p)^{m}s^{m} $$ by (1) which is the pgf of the negative binomial distribution as follows.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.